The role of traditional birth attendants and problem of integration with health facilities in remote rural community of West Omo Zone 2021: exploratory qualitative study - Aychew Kassie; Alemnew Wale; Desalegn Girma; Hailemariam Amsalu; Mastewal yechale (BMC, 2022)
Abstract Background Mothers in rural Ethiopian communities prefer giving birth at home. In developing countries, traditional birth attendants play an important role in reducing the maternal mortality rate. In Ethiopia, however, their role during pregnancy, childbirth, the postnatal period, and their integration with health professionals is not clearly defined. This study aimed to explore the role of traditional birth attendants in feto-maternal care during pregnancy, childbirth, and the postnatal period, and integration with health professionals in the West Omo Zone, southern Ethiopia. Methods A qualitative descriptive design was used with triangulation of methods and data sources. We conducted in-depth interviews with traditional birth attendants, key informant interviews with health care professionals and community or religious leaders, and two focus group discussions with multiparous pregnant women. Each interview and focus group discussion was tape-recorded and the data obtained were transcribed and translated into English for analysis. The analysis was done based on thematic analysis framework. Results Traditional birth attendants stated that they used herbal remedies to treat nausea and vomiting, decrease pain during labor, and increase pregnant women's desire to push. The absence of incentives for their work, shortage of logistics, and lack of training was mentioned as challenges to the continuity of their roles. All study participants explained the importance of training traditional birth attendants on maternal and child health in rural communities. However, health care professionals reported that few traditional birth attendants advised mothers about traditional practices such as milk tooth extraction and uvulectomy. Conclusion and recommendation Traditional birth attendants continued their roles despite the existing challenges. There was no integration between TBA and the formal health care system. The need for training traditional birth attendants has been emphasized by all study participants and its impact on reducing feto-maternal death was recognized by health care professionals. Therefore, the federal ministry of health should works better for the development of TBAs to scale up their skills across all regions in the country.